Works of the Right Reverend George Bull, D.D. ...: concerning the Holy Trinity ... - Bull, George (Printed for Stephen Austen, 1730)
I. The defence of the Nicene Creed. -- II. The judgment of the Catholick Church of the three first centuries. -- III. The Primitive and Apostolical tradition concerning the received doctrine in the Catholick Church.